The lateral wrist radiograph - To retake or not to retake. Issue 1 (January 2023) - Mussmann, B.R.; Milner, Robert; Barlow, Nicholas; Jensen, Janni
Abstract: Introduction: Patient positioning may impact diagnostic quality when obtaining radiographs of the musculoskeletal (MSK) system. Hence, knowledge on patient positioning, as seen in the radiograph, followed by informed adjusted retake if appropriate, is key when undertaking MSK radiographs. Forearm positioning is particularly important in lateral wrist radiographs where rotation impacts anatomic measurements. The purpose was to evaluate the accuracy of MSK and non-MSK radiographers' immediate assessments of wrist positioning including need for retake. Methods: A questionnaire including images of 18 lateral wrist radiographs and questions regarding positioning, i.e. forearm rotation and flexion of the wrist, were developed and distributed to radiographers worldwide via the European Federation of Radiographer Societies (EFRS) and the Research Hub at the European Congress of Radiology (ECR) 2021. Demographic data such as area of expertise, years of experience etc. were collected. Results: In total, 156 replies were included in the analyses. The inter-observer agreement of radiographers' assessment of the need for a retake was 47% (kappa = .25) and the intra-observer agreement was 81% (kappa = .62). Radiographers working with MSK radiography had more correct positioning assessments than radiographers who did not routinely obtain radiographs of the MSK system (p = 0.0003). Conclusion: Results indicated that MSK radiographers are more consistent in assessment of the need for a retake in lateral wrist radiographs and more able to correctly judge positioning compared to non-MSK radiographers. Implications for practice: Constant focus on image quality may lead to increased awareness and adherence to image criteria. Improved image quality will in turn improve the diagnostic value for the benefit of the patients potentially leading to better outcomes.